Avoiding stimulus confounds in Implicit Association Tests by using the concepts as stimuli. - Steffens MC; Kirschbaum M; Glados P (British Journal of Social Psychology, 2008)
Implicit Association Tests (IATs) are supposed to measure associations between concepts. In order to achieve that aim, participants are required to assign individual stimuli to those concepts under time pressure in two different tasks. Previous research has shown that not only the associations of the concepts with each other, but also the stimuli's cross-category associations influence the observed reaction time difference between these tasks (i.e. the IAT effect). Little is known about adequate stimulus selection. In this article, we introduce a variant of the IAT, the Concept Association Task (CAT) in which the concepts themselves or synonyms of them are used as stimuli. Three experiments on Germans' attitudes towards foreigners yielded evidence for the convergent validity of the CAT: (1) it correlated well with other IAT versions; (2) it correlated higher with spontaneous attitude-related judgements than other IAT versions; and (3) it correlated with response-window priming, another implicit measure based on reaction times. Furthermore, we showed that the CAT yielded reasonable findings when other IAT versions appear to yield distorted ones.